2022
DOI: 10.1002/jcv2.12093
|View full text |Cite
|
Sign up to set email alerts
|

Early manifestations of genetic liability for ADHD, autism and schizophrenia at ages 18 and 24 months

Abstract: Pregnant women resident in Avon, UK with expected dates of delivery 1st April 1991 to 31st December 1992 were invited to take part in the study. The initial number of pregnancies enrolled is 14,541 (for these at least one questionnaire has been returned or a "Children in Focus" clinic had been attended by 19/07/99). Of these initial pregnancies, there was a total of 14,676 foetuses, resulting in 14,062 live births and 13,988 children who were alive at 1 year of age. When the oldest children were approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 76 publications
3
14
1
Order By: Relevance
“…For example, more research is needed on how PRS associates with precursors and early markers of ADHD. Second, the study by Riglin et al (2022) Second, because of a lack of ancestral diversity in currently available GWAS, individuals were excluded from the analyses on the basis of non-European ancestry, which limits generalisability. Investments are needed to perform large-scale GWASs in globally diverse populations.…”
Section: Polygenic Risk Scores and Adhdmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, more research is needed on how PRS associates with precursors and early markers of ADHD. Second, the study by Riglin et al (2022) Second, because of a lack of ancestral diversity in currently available GWAS, individuals were excluded from the analyses on the basis of non-European ancestry, which limits generalisability. Investments are needed to perform large-scale GWASs in globally diverse populations.…”
Section: Polygenic Risk Scores and Adhdmentioning
confidence: 99%
“…Third, while PRSs are useful for studying correlations, they cannot be taken as evidence of causality. Riglin et al (2022) correctly point out that they cannot differentiate whether motor development and temperament lie on the causal pathway between genetic liability to neurodevelopmental conditions and later neurodevelopmental conditions, if these associations arise independently as the result of (horizontal) pleiotropy, or whether the associations reflect an early manifestation of neurodevelopmental conditions. Implementation of sophisticated study designs and analyses will probably help uncover the mechanisms underlying identified PRS associations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations